Hubungan Beban Kerja Dosen berdasarkan Time and Motion Study dengan Kinerja Dosen Prodi S1 Ilmu Keperawatan Stikes Surabaya - Taufan Citra Darmawan (Bahasa Indonesia, 2018)
Nursery education needs profesional and qualified graduates. The achievement in the quality of education depends on lecture espicially the labor of lecturer. The achievemen of lecture’s in quality, bring about Tridharma of university became the first duty of lecturer, furthermore the purpose of this research is to know the relation between with responsibility towards lecturer’s perfomance. This research use observational analysis method, with cross-sectional as the main framework in this research. This sample use total sampling method. The sample of this research are 7 personel of lecturers which department of S1 Nursery Science STIKES Surabaya, did by observation and questionnaire as the method of collect the data. Mostly, work responsibility of lecture is on the middle category is 4 (57%) lecturers, the lecture perfomances are categorized as Good and Enough with the same result 3(43%). The result of this research use bivariant analysis by pearson correlation test are (p = 0,011, r = 0,867) where the false degree α ≤ 0,05 which means H1 accepted. It;s meanthere is a relation between work responsibility of lecture with lecturer’s perfomance in Departement of S1 Nursery Science STIKES Surabaya. Lectures with high perfomancecan’t leave that student’s study. And lecturer with low perfomance must be fixed their self.